Empowerment of Muslim Communities Through the Use of Village Funds (Case Study of Aek Tapa Labuhanbatu Utara Village) - Tanjung, Arfan; Qarni, Waizul; Silalahi, Purnama Ramdani (LPPPM STAI Darul Hikmah Bangkalan, 2025)
This study aims to analyze the empowerment of the Muslim community through the use of Village Funds in Aek Tapa Village, North Labuhanbatu Regency. The research method used is a descriptive qualitative approach with the Triple Helix model which involves synergy between the government, the community, and academics. Primary data was obtained through interviews with village officials, while secondary data came from the 2024 APBDes realization document and related literature. Data collection techniques include literature studies, documentation, and field research. The results of the study show that the use of Village Funds in Aek Tapa Village has significantly improved the quality of life of the Muslim community. The programs implemented, such as infrastructure development, entrepreneurship training, and empowerment of Village-Owned Enterprises (BUMDes), have contributed to increasing household income and community participation in economic activities. In addition, the strengthening of Islamic values is also reflected through the construction of informal educational institutions, such as Madrasah Diniyah and TPA, as well as the implementation of religion-based social programs. However, there are several challenges, such as lack of community participation in program planning and limited capacity of village governments in managing funds optimally. To overcome this obstacle, it is necessary to increase community involvement, fund management training for village officials, and develop a better monitoring and evaluation system. Triple Helix Proven Approach effective in improving community welfare through inclusive and sustainable management of Village Funds.